Against nature - Daston, Lorraine 1951- (MIT Press, 2019)
The problem -- Specific natures -- Local natures -- Universal natural laws -- The passions of the unnatural -- The very idea of order -- The plenitude of orders -- Saving the phenomena
Includes bibliographical references
Keywords: Geschichte; Philosophische Anthropologie; Natur; Naturrecht; Begriff; Ethik; Naturphilosophie; Rechtsphilosophie; Philosophical anthropology; Philosophy of nature; Ethics